The experience and communicative management of identity threats among people with Parkinson's disease: Implications for health communication theory and practice. Issue 3 (2nd July 2016) - Martin, Summer C.
ABSTRACT: Parkinson's disease (PD) is a progressive, neurodegenerative illness that can yield a host of well-documented physical and psychosocial challenges; however, the impact of the disease on the identity of persons with PD (PWPs) is not well understood. Based on a constructivist grounded theory approach, data gathered from in-depth interviews with 47 PWPs were analyzed using constant comparison. The resulting theoretical structure related to identity and communication states that (a) PD threatens identity in several significant ways; (b) PWPs communicatively manage threats to identity; and (c) communicatively managing threats to identity is a complex, varied process. Results offer a theoretical understanding of the ways in which identity, communication, and PD are linked, and can inform interventions and care for this population.